MOGID : Mobile Geo-depended Information on Demand - Balsiger, Peter; Sun, Dequn; Gomez, Manuel; Pellandini, Fausto; Aeschlimann, Marcel; Dworzak, Christophe; Hubmann, Michael; Sollberger, Alex (My University, 2000)
This paper outlines possible areas of cooperation between the WAP Forum, the World Wide Web Consortium (W3C) and the mobile terminal provider and Value Added Service (VAS) providers. The WAP Forum is dedicated to enabling advanced services and applications on mobile wireless devices, such as cellular telephones. The W3C is dedicated to leading and advancing the development of the World Wide Web. This document describes the MOGID solution of mobile access to efficient information seeking. MOGID is a GSM based positioning system built inside the GSM standard and share goals for the future of the global information space. MOGID avoids unnecessary divergence between the recommendations and standards of the GSM standard and the WAP and W3C organizations. Future development occur in the areas of Intelligent Value Added Services (iVAS) based on WAP and W3C standards by the combination of user location information. MOGID fits in this direction.